Increasing Discovery in Research, Design, and Other Processes with Artificial General Intelligence and General Collective Intelligence - Williams, Andy (My University, 2020)
Any system with repeatable behavior can potentially be defined with the minimal set of functions that might be composed to represent the entirety of that behavior. The states accessible through these functions then forms a “functional state space” through which the system moves. Since functional states spaces can be used to represent every problem domain from physics, to communications, to business operations, to the human cognition itself, a general approach to not only research but design and all other processes of discovery that is applicable to all domains can potentially be defined to radically increase capacity for discovery in each domain.
Keywords: Artificial General Intelligence; General Collective Intelligence; research impact; innovation